Non-Residence in the Lincoln Diocese in the Early Sixteenth Century - Bowker, Margaret (The journal of ecclesiastical history, 1964)
In his Introduction to The Visitations in the Diocese of Lincoln 1517–1531, the late Professor Hamilton Thompson drew attention to the large number of pluralist and non-resident parish priests in the diocese in the early part of the sixteenth century. He could do no more than comment on a few cases, since the scribe did not bother to include in the comperta the names of all delinquents, their alleged reasons for non-residence nor the details about their licences. More recently attention has been drawn to the actual number of non-residents, but no attempt has been made to go behind the figures to the individual priests and parishes concerned.